Exploring the Values of Local Wisdom as Sustainable Tourism Attractions - Andari, Rini; Supartha, I Wayan Gede; Riana, I Gede; Sukawati, Tjokorda Gde Raka (International Journal of Social Science and Business, 2020)
Sustainable tourism is a concept that is aspired to be realized in the tourism industry so that natural and cultural resources can be preserved and enjoyed for generations to come. This research explores a variety of tourist attractions based on local wisdom values as an effort to create sustainable tourism. Kampung Banceuy is one of the traditional villages that has various values of local wisdom which is still preserved today and is able to attract many tourists. The method used in this research is an explorative qualitative approach. The data collection technique is done by direct observation, interviews, and documentation. Data analysis techniques were carried out in an interactive way and continued until completion, so that the data was saturated. The informants in this study were 9 people consisting of traditional leaders, communities, tourism managers, and tourists. The results showed that the value of local wisdom that can be a tourist attraction is village celebration events, cultural festivals, natural tourist attractions, and community life that has educational value. These various tourist attractions are not only oriented towards economic benefits but also act as a medium for the conservation of noble socio-cultural and environmental values as well as having educational value for tourists through the experience of tourism activities. The practice of the value of local wisdom that is still maintained is expected to always be passed on to the younger generation and can be of benefit to many parties, therefore this tourism activity always requires support from various parties.